Determinan terhadap perkembangan UMKM di Kabupaten Pemalang - Handayani, Nurdiana; Badjuri, Achmad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Several factors that support the economic growth of a country, namely the existence of MSMEs. Micro, small and medium enterprises (MSMEs) can open or expand employment opportunities and contribute to economic growth. In addition, MSMEs can ease the task of the state in overcoming poverty and increase per capita income because MSMEs play a major role in the Indonesian economy. This study aims to determine the effect of financial literacy and financial technology (Fintech) on the development of MSMEs in Pemalang Regency. This research uses a qualitative research. The research was conducted in Pemalang Regency. Data sources are primary data with data collection methods, namely direct interviews at the object of research and secondary data support from the Pemalang Regency Diskoperindag. Data analysis used multiple linear regression. The results of the study show that financial literacy has a positive and significant effect on the development of MSMEs in Pemalang Regency. Financial technology (Fintech) related to payments has no effect on the development of MSMEs in Pemalang Regency. Meanwhile, financial technology (Fintech) related to funding has a negative and significant impact on the development of MSMEs in Pemalang Regency.